2022
DOI: 10.1021/acs.inorgchem.1c03371
|View full text |Cite
|
Sign up to set email alerts
|

Carbene–Metal Complexes As Molecular Scaffolds for Construction of through-Space Thermally Activated Delayed Fluorescence Emitters

Abstract: The through-space charge transfer (CT) process is observed in Cu(I) carbene−metal−amide complexes, where conventional imidazole or imidazoline N-heterocyclic (NHC) carbene fragments act as inert linkers and CT proceeds between a metal-bound carbazole donor and a distantly situated carbenebound phenylsulfonyl acceptor. The resulting electron transfer gives a rise to efficient thermally activated delayed fluorescence (TADF), characterized with high photoluminescence quantum yields (Φ PL up to 90%) and radiative … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 58 publications
0
21
1
Order By: Relevance
“…Finally, the Au‐based complex 6 a bearing another widely used NHC, IMes (IMes= N,N ′‐bis‐(2,4,6‐trimethylphenyl)imidazol‐2‐ylidene), was also obtained in high yield. To the best of our knowledge, a heterocyclic amine‐based CMA with the metal/NHC combination of 5 a was only very recently reported for the first time, [24] while a heterocyclic amine‐based CMA with the metal/NHC combination of 6 a is reported here for the first time.…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…Finally, the Au‐based complex 6 a bearing another widely used NHC, IMes (IMes= N,N ′‐bis‐(2,4,6‐trimethylphenyl)imidazol‐2‐ylidene), was also obtained in high yield. To the best of our knowledge, a heterocyclic amine‐based CMA with the metal/NHC combination of 5 a was only very recently reported for the first time, [24] while a heterocyclic amine‐based CMA with the metal/NHC combination of 6 a is reported here for the first time.…”
Section: Resultsmentioning
confidence: 82%
“…The latter cases have received comparatively much less attention because of limited potential for OLED materials applications, even though recent advances show that modifications of the acceptor imidazol(in)ylidene ligand enable throughspace TADF. [24] Importantly, applications beyond TADF are possible when using imidazol(in)ylidene-based CMAs, with recent examples being long-lived room temperature phosphorescence (RTP), [18] and photocatalysis by triplet energy transfer. [22] For the latter application, the choice of the carbene ligand and the metal, Au in particular, is paramount as weaker π-acceptors enable longer-lived triplet states and the strong spin-orbit coupling (SOC) of the heavy metal atom enables efficient intersystem crossing (ISC), thus these compounds emit solely via phosphorescence, in addition to being more photolytically stable than their Ag congeners.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach provides the additional advantage of various coordination spheres of the same metal centre being accessible, which greatly influences the nature, energy and reactivity of the excited states. Extensive work on trigonally and linearly coordinated Cu I compounds, in particular, has shown that very efficient triplet state decay can be obtained either by phosphorescence, [20,24–26] or thermally activated delayed fluorescence (TADF) [10,21,27–29] . For this, the ideal molecular structure should allow for the formation of low‐energy ligand‐to‐ligand charge transfer (LLCT) states with some metal‐to‐ligand (ML)CT admixture to mediate spin‐orbit coupling (SOC).…”
Section: Introductionmentioning
confidence: 99%
“…18,19 In these complexes, a cyclic (alkyl)(amino)carbene (CAAC) ligand serves as electron acceptor from the (amido) metal(I) fragment, leading to conformationally dependent delayed fluorescence. One example is the work of Traskovskis and co-workers 20 who demonstrate that sulfonyl-substituents in the N-aryl moieties of (NHC)Cu(I) and -Ag(I) complexes reinforce charge transfer, resulting in thermally activated delayed fluorescence, in another instance of carbene-modulated luminescence. Thompson and co-workers described a digold(I)-amide complex where the supporting carbene ligand is a binuclear gold(I) construct.…”
Section: Introductionmentioning
confidence: 99%